2017
DOI: 10.1155/2017/5242048
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Administration of Medication without Prescription and Associated Factors among Preschool Children

Abstract: The increasing trend of administering nonprescribed medicines in children is a significant public health issue. The aim of the present study was to assess the use of medication without a prescription (MWP), including both nonprescribed medication (NPM) and prescription-only medication (POM), and identify associated factors, among preschoolers in Athens, Greece. A predesigned questionnaire was distributed to parents from May through June 2011. Multivariable binary logistic regression analysis models were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
2
7
0
2
Order By: Relevance
“…The results of the current study indicated that there were statistically significant differences found between socio-demographic characteristics of the studied mothers' and their total score of knowledge about practice in pre and posttest for all item as shown in Table 8. These findings were similar to a study carried out by [21], [38], [39] and [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study indicated that there were statistically significant differences found between socio-demographic characteristics of the studied mothers' and their total score of knowledge about practice in pre and posttest for all item as shown in Table 8. These findings were similar to a study carried out by [21], [38], [39] and [12].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, most of them gave previously prescribed antibiotics, antipyretics, cough and cold medications to their children without prescription as illustrated in Table 5, Table 6. The results were in the same line with [16,20,21,22,23,24] they indicated that there was a high prevalence of non-prescribed medications among children.…”
Section: Discussionsupporting
confidence: 75%
“…Acetaminophen is the most commonly used antipyretic medication in children and is also often used to treat pain [1]. Although hepatotoxicity related to acetaminophen overdosing has been well documented [2], acetaminophen hypersensitivity is a rare event [3], and very little is known about the hypersensitivity reactions related to appropriate dosing.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to 77% reported in Pakistan 7 and higher than the prevalence of 32% and 58.82% reported in Madagascar and India 8,11,16 . However, higher prevalence of 95.1% and 98.1% were reported in Greece and Australia 17,18 . This shows that self-medication in children is a universal practice with some differences between countries.…”
Section: Discussionmentioning
confidence: 88%
“…Factors associated with the parental choice to self-medicate their children vary, but include: parents/caregivers perceiving their child's illness as being mild and not requiring health professional consultation, lack of time to attend consultations, high consultation fees, clinic waiting time, emergency treatment, use of old prescriptions available in the home, parent comfort in recognizing their children's disease based on the symptoms and having experience with the medication 14,15 . Pediatric self-medication is a worldwide practice with a reported prevalence between 32-98% in Madagascar, India, Greece, and Australia 8,[16][17][18] . Tanzania, a fellow nation of the East African community has reported pediatric self-medication rates of 69% 19 .…”
Section: Introductionmentioning
confidence: 99%